If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x+3=-4x+10
We move all terms to the left:
-5x+3-(-4x+10)=0
We get rid of parentheses
-5x+4x-10+3=0
We add all the numbers together, and all the variables
-1x-7=0
We move all terms containing x to the left, all other terms to the right
-x=7
x=7/-1
x=-7
| 5.1=j÷2+2.1 | | 4f-3.32=16.68 | | 5.23=-d+3.75 | | 2n^2-5n-25;=0 | | -6x-14=-2x+2 | | w2^–12w=-36 | | -x-7=13 | | x4-3=0 | | -6x+18=-4x+30 | | 7•x-40=30 | | f(53)=(2(53)-6) | | -4x=30-2x | | 8.30-2.75+h=789 | | 6+4x-x2=0 | | r2^+12=61 | | -21=x^2+10x | | s2^-25=-25 | | -21=x^2+10 | | 5x–2= | | 4x−7−2x=−3 | | -8x-3=-5x-9 | | 3x-8=-x-20 | | 3x−12+x=8 | | 355–5x=177.5 | | 355–6x=178.5 | | x^2+3x-5/4=0 | | 5x-11=-x+7 | | 7x+17=4x+14 | | 2n+5=9(n=2) | | |3x+5|+|4x+7|=12 | | -6x-4=-3x-28 | | -7x+17=-5x-1 |